Environmental Education as a Means for Valuing and Conserving Camelids and Pastoralism in the Argentinean Altiplano of Jujuy - Vila, Bibiana Leonor (2020)
Andean pastoralism, like other pastoral systems around the world, is under stress due to climate change, land tenure regimes, pressures to become sedentary, difficulties in interacting with market-based economies, isolation, and youth emigration. Over the years, we have proposed different environmental education (EE) strategies targeting local Andean stakeholders and university students, including interventions in primary schools. This paper presents the results of 4 EE interventions focusing on mountain environments, their biodiversity, environmental calendars, and llama caravans. School children participated creatively in this process by writing poems, drawing, and playing. The resulting work showed sensitivity, experiential knowledge, and a comprehensive vision of the environment. Most of the artworks were printed and disseminated in the children's local communities, where they are highly appreciated. We recognize that the usefulness of EE is constrained by social and economic pressures, including extractive activities. However, we also underscore its huge potential to guarantee sustainability during the inevitable process of change in traditional Andean pastoralism.